МЕТОДИКА ВОКАЛЬНО-ХОРОВОЇ РОБОТИ З УЧНЯМИ НА УРОКАХ МУЗИКИ (Педагогіка вищої та середньої школи, 2004)
On a present day stage of development of musical pedagogics the problem of forming of vocal-choral skills in the  process of pupils’ education is the most actual. The vocal-choral singing takes a special place in the aesthetical and artistic pupils' upbringing.